111In-labeled immunoconjugates (ICs) bispecific for the epidermal growth factor receptor (EGFR) and cyclin-dependent kinase inhibitor, p27Kip1. - Cornelissen, B; Kersemans, V; McLarty, K; Tran, L; Reilly, R (2009)
OBJECTIVE: Probing intranuclear proteins in breast cancer (BC) cells by using radiolabeled antibodies is restricted by delivery barriers presented by cell and nuclear membranes. Our aim was to construct immunoconjugates (ICs) bispecific for epidermal growth factor receptors (EGFRs) and the intranuclear cyclin-dependent kinase inhibitor (CDKI) p27(Kip1) modified with nuclear-localizing sequences (NLSs) to facilitate their nuclear uptake following EGFR-mediated internalization. METHODS: Bispecific ICs were constructed by first modifying EGF with peptides [GGPKKKRKVGYGCG] harboring NLS from SV-40 large T-antigen (underlined), then conjugating NLS-EGF to anti-p27(Kip1) antibodies through an extended PEO(12)-maleimide linker (Compound 1). Analogous ICs were constructed by using mouse IgG (Compound 2), a disrupted NLS (Compound 3) or omission of the EGF moiety (Compound 4). Binding to EGFR on MDA-MB-468, H2N, or HR2 BC cells and to p27(Kip1) in HELA cell lysate was measured. Internalization and nuclear importation were evaluated. Retention of the ICs in H2N or trastuzumab (Herceptin)-resistant HR2 cells exposed to trastuzumab to modulate p27(Kip1) expression with/without coexposure to the IGF-1 receptor kinase inhibitor, AG1024, was determined. RESULTS: Trastuzumab (10 microg/mL) unexpectedly decreased p27(Kip1) expression by 1.7-2.4-fold in H2N or HR2 cells. Conjugation of EGF to anti-p27(Kip1) antibodies (Compound 1) decreased the binding affinity of the ICs 7-fold toward EGFR and p27(Kip1). All ICs bound EGFR on MDA-MB-468 cells except Compound 4. Compound 1 was internalized into H2N cells over 48 hours and Compound 2 exhibited 1.6-fold greater nuclear importation in H2N or MDA-MB-468 cells than Compound 3. There was a significantly lower retention of Compound 1 in H2N cells exposed to trastuzumab, compared to unexposed cells, corresponding to decreased p27(Kip1), but in HR2 cells, diminished retention was observed only when these cells were coexposed to trastuzumab and AG]024. CONCLUSION: We conclude that (111)In-labeled bispecific ICs were constructed that specifically bound EGFR and p27(Kip1). These ICs were internalized into BC cells expressing EGFR and HER2 and imported into the nucleus. Their decreased retention by cells with trastuzumab-modulated p27(Kip1) suggests that they may be useful for probing this CDKI by imaging.